Principles of risk analysis : decision making under uncertainty - Yoe, Charles E. (Boca Raton, FL : CRC Press, 2012)
'Preface I did not want to write this book. I wanted to buy it. Risk analysis is mature enough that it needs a principles text. There are many wonderful books available on the subject of risk. In fact, for years, in the training I have done, I used to schlep a dozen of them around for students to peruse. These I called the starter library. I urged people to buy them. Eventually I stopped carrying the books with me and started looking for that one book that would introduce students and professionals to the integrated topic of risk analysis. I never found it. So, I decided to go ahead and write it. Risk analysis is a very parochial subject matter and practice. There are many tribes of risk practitioners, and they speak many dialects. To be honest, I am not entirely sure the field is ready for anything one might call a principles text. We may never have enough agreement on the principles to so ordain them as a community of practice. Nonetheless, it has been my great fortune to have worked with a lot of people on many different applications of the risk analysis decision-making paradigm. This has included natural disasters, engineering, food safety, food defense, environmental issues, animals and plants, trade, quality management, business, finance, terrorism, defense applications, research, and other risk analysis applications. No matter how much the words and models changed from one application to the next, I found the basic principles were rather constant. Everyone was struggling to figure out how best to make good decisions when there are so many things we just don't know for sure. My major accomplishment in all of this was simply to learn the jargon of each field; then I stole liberally from the other fields, adapting ideas, methodologies, and models from one field'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Decision making; Risk assessment